Estetica e politiche culturali europee. La specificità del lavoro artistico fra poiesis e téchne - Evola, Dario (Aesthetica Preprint, 2023)
The aim of European cultural policies is to build a cultural identity in a common training path. Artistic practices, training and research constitute one of the best practices for social relations. Knowledge of the artistic function has a fundamental role in the knowledge of cultural heritage such as social growth, inclusion, ethical participation. The Academies, Universities, Museums collaborate in the training and knowledge of art mediated by artistic operations. Aesthetics is characterized as a discipline of training and Art as a gaze mediated by the artist, as learning by doing. A European project between the Academies of Budapest, Dresden, Riga and Rome works for the construction of a Lexicon for artistic techniques and poetics as a tool for teaching and research.